THE RELEVANCE OF ETHNOBOTANICAL STUDIES TO LINGUISTIC VITALITY: THE CASE OF PLANT USE AND CLASSIFICATION AMONG THE DIGO OF KENYA (The University of Nairobi Journal of Language and Linguistics, 2023)
This article summarises the findings of ethnobotanical research conducted among the Digopeople of Kwale District, Kenya, together with applications of this research for the benefit ofthe local community and implications of this for language vitality. The article consists of foursections. Section 1 provides background information on the Digo people and language, theecology of the region, and the research methodology employed. Section 2 discusses Digobotanical folk taxonomy, that is, the way in which Digo speakers classify plants, and the waysin which this differs from botanical folk taxonomies reported for neighbouring Swahilispeakers. Section 3 provides details of medicinal and other uses of a sample of 30 plants.Finally, in Section 4 the relevance of such studies is related to the current debate on themaintenance and interrelation of linguistic, cultural and biological diversity.